Pengaruh Disiplin Kerja Terhadap Kinerja Pegawai Pada Dinas Sosial Pekanbaru - Khornelis Dehotman (Sekolah Tinggi Ilmu Ekonomi Riau, 2025)
This study aims to determine the effect of work discipline on employee performance at the Social Service Office of Pekanbaru City. Work discipline is one of the key factors in developing high-quality human resources, especially in government institutions that are required to provide optimal services to the public. This research uses a quantitative approach with a survey method, where data were collected through questionnaires distributed to the entire population of 34 employees. The data analysis technique used is simple linear regression to examine the relationship between work discipline as the independent variable (X) and employee performance as the dependent variable (Y). The results of the simple linear regression equation show a constant (a) of 9.852, meaning that when work discipline (X) is zero or absent, employee performance (Y) is still at 9.852 units. The effect of work discipline (X) on employee performance (Y) is positive, as evidenced by the regression coefficient (b) of 0.717, which means that every one-unit increase in work discipline (X) will increase the employee performance (Y) at the Social Service Office of Pekanbaru by 0.717 units. Based on the t-test results, the calculated t-value is 4.791, which is greater than the t-table value of 2.036, and the significance level is 0.000 < 0.05. This indicates that there is a significant effect of work discipline on employee performance at the Social Service Office of Pekanbaru. The R Square value is 0.418, which means that the contribution of work discipline to employee performance is 41.8%. The remaining 58.2% is influenced by other variables not discussed in this study.